2023
DOI: 10.3390/app13074277
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of a Bacteriocin Produced by Lactobacillus pentosus 124-2 Isolated from Dadih

Abstract: The fermentation process results in the presence of lactic acid bacteria (LAB). Traditional fermented buffalo milk from the Indonesian province of West Sumatra is known as dadih. Bacteriocins are naturally occurring antimicrobial peptides that can be produced by LAB. These bacteriocins have the potential to be used as natural preservatives. This research was conducted with the intention of isolating and partially characterizing a bacteriocin that was generated by Lactobacillus pentosus 124-2 that was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…In a previous study, Yuliana et al discovered that Lactobacillus pentosus 124-2 was identified as the strain of LAB in dadih [18]. CFS containing metabolites from Lactobacillus pentosus 124-2, especially organic acids such as lactate, acetate, citrate, formate, and succinate, may have potential to preserve high-protein foods, such as beef.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Yuliana et al discovered that Lactobacillus pentosus 124-2 was identified as the strain of LAB in dadih [18]. CFS containing metabolites from Lactobacillus pentosus 124-2, especially organic acids such as lactate, acetate, citrate, formate, and succinate, may have potential to preserve high-protein foods, such as beef.…”
Section: Introductionmentioning
confidence: 99%